La voie du syncrétisme : sur la musique électroacoustique au Brésil - Menezes, Flo (Circuit, 2007)
This text deals with certain aspects of the birth of electroacoustic music in Brazil, by making links between Brazilian contemporary music and economic, political and social circumstances of the country’s history. After describing the emergence of a cannibalistic movement in Brazilian culture, i.e., of musical nationalism, the author seeks to situate the first attempts in the genre and to shed light on the circumstances surrounding the establishment of the first centre of research and production of electroacoustic music in Brazil: Studio panaroma in São Paulo.